MORPHOLOGICAL CHANGES AFTER RECONSTRUCTIVE BLADDER SURGERY (Лучшие интеллектуальные исследования, 2025)
Reconstructive bladder surgery, which involves the use of intestinal segments, is mainly performed to treat acute bladder trauma, tumors, or congenital anomalies. After such surgery, the "new" bladder undergoes morphological changes related to the adaptation of intestinal tissues, epithelial differentiation, and reorganization of muscle layers. This article provides a detailed account of these changes